Corrigendum to “flexible chain-engineered conjugated polymers with phosphonic acid anchors for synergistic photocatalysis-adsorption uranium extraction” [Chem. Eng. J. 521 (2025) 166451] - Yuanping Jiang; Feng Wang; Junshuo An; Xingfang Yu; Menghan Cao; Guohang He; Danning Xu; Jiajian Yang; Kai Zhang; Yunxiu Zhang; Lin Xu; Zuojia Li; et al. (Chemical Engineering Journal, 2026)

Synergistic alkaline etching and nitrogen lattice occupation strategy enables gradient defluorinated cathode for high-performance Li/CFx batteries - Hongwei Cai; Xiaoxiao Pan; Cong Li; Hao Luo; Menghan Lin; Mingyi Shang; Jiqiong Lian; Yanan Fu; Hongjun Yue; Huixin Chen; Xiaolong Li; Yujin Tong; et al. (Chemical Engineering Journal, 2026)

Adaptive Multi-Scale Frequency-Domain Reconstruction for Multi-Source Gravity Data Fusion - Menghan Xi; Lin Wu; Zuoqin Shi; Qianqian Li; Shi Liu; Lifeng Bao (Journal of Marine Science and Engineering, 2026)
The gravity navigation reference map is a foundational element of gravity matching-aided navigation systems, as it directly determines positioning accuracy and overall navigation performance. To improve fused gravity anomalies and reduce reliance on manually selected parameters, this study proposes an adaptive multi-scale frequency-domain reconstruction (AMFR) algorithm. Specifically, the target ocean covered by multi-source satellite gravity data is divided into multiple scales, and distinct fusion parameters are assigned according to the characteristics of multi-source gravity data in different sea areas to enhance the accuracy of the fused gravity navigation reference map. Seven fusion schemes with different filtering diameters and weighting strategies are designed for comparative analysis. We evaluate the algorithm’s performance using measured gravity data with varying spatial distributions from the South China Sea and the Western Pacific Ocean, employing both RMS comparison and matching positioning experiments. Experimental results demonstrate that the RMS of the gravity navigation reference map constructed by the proposed AMFR algorithm is reduced by 30.4%, and the matching positioning accuracy is improved by 23.4%. The AMFR algorithm effectively enhances the precision of the gravity navigation reference map and improves the navigation performance of the gravity matching-aided navigation system.

Synergistic effects of biochar application and wide-precision planting on wheat yield: Optimizing canopy structure and facilitating deep root growth - Menghan Jia; Jiayue Dai; Zeping Shi; Yehan Fu; Yu Cheng; Yixuan Lin; Baodi Dong; Lijuan Zhang; Yuzhao Ma (Field Crops Research, 2026)

Pasteurella multocida toxin induces apoptosis of respiratory epithelial cells by activating the PERK–NF-κB-DR5 signaling axis - Fei Wang; Yuhao Lei; Menghan Chen; Haixin Bi; Yayuan Luo; Fangfang Bai; Lin Hua; Huanchun Chen; Qigai He; Bin Wu; Zhong Peng (Veterinary Microbiology, 2026)

Hydrogeochemical properties and health risks of high-fluoride groundwater in southern Jiaolai Basin - Menghan Tan; Zongjun Gao; Jiutan Liu; Bing Jiang; Linlin Lin; Qiang Li; Yiru Niu (Process Safety and Environmental Protection, 2026)

Histone H3.3 phosphorylation facilitates H3K9me3-heterochromatin formation during retrotransposon silencing and X-chromosome inactivation via H3.3K27me3–CBX7–KAP1 axis - Jun Chen; Jiyu Chen; Zhouliang Yu; Liwei Zhang; Yanchao Liu; Xuan Ouyang; Juan Yu; Menghan Wang; Shangqiang Xie; Ming Wang; Tiantian Zhang; Zhaohui Jin; et al. (Science Bulletin, 2026)

Whole-genome sequencing of Listeria monocytogenes isolated from retail enoki mushrooms in China highlights public health risk - Jianyun Zhao; Lanqi Li; Menghan Li; Dajin Yang; Lin Yan; Yingying Nong; Shaofei Yan; Li Bai (International Journal of Food Microbiology, 2026)

Late Holocene extreme dust events in the arid Central Asia recorded by lake sediments in Tien Shan - Min Zheng; Xiaozhong Huang; Ning Wang; Menghan Qiu; Jun Zhang; Lixiong Xiang; Shaojun Chen; Muhammad Farqan; Ruiqi Min; Tao Wang; Chong Huang; Xiuxiu Ren; et al. (Quaternary Science Reviews, 2025)

Flexible chain-engineered conjugated polymers with phosphonic acid anchors for synergistic photocatalysis-adsorption uranium extraction - Yuanping Jiang; Feng Wang; Junshuo An; Xingfang Yu; Menghan Cao; Guohang He; Danning Xu; Jiajian Yang; Kai Zhang; Yunxiu Zhang; Lin Xu; Zuojia Li; et al. (Chemical Engineering Journal, 2025)

A Deep Learning Framework for Parameter Estimation in 1D Marine Ecosystem Model - Ao Li; Kewei Zhao; Weiwei Fang; Chan Shu; Runjie Zhou; Qiuyi Li; Xiaolong Huang; Xiaohong Lei; Menghan Xu; Haoyu Jiang; Lin Mu (Journal of Marine Science and Engineering, 2025)
Marine ecosystems play an increasingly critical role in both global climate regulation and the impacts of anthropogenic activities. Accurate marine biogeochemical numerical models are essential tools for understanding and predicting the complex dynamics of these systems. However, as model complexity increases, so does the number of biological parameters and the uncertainties associated with them, which can substantially affect model performance. Consequently, efficient and reliable parameter estimation has become a key challenge in model development and application. In this study, we proposed a deep learning-based approach for parameter estimation in numerical models, utilizing deep neural networks to capture the complex nonlinear relationships between numerical model input parameters and output variables. A one-dimensional marine ecosystem model is employed as a case study to evaluate the effectiveness of the proposed method. The results demonstrate that (1) the deep learning approach provides an automated and adaptive solution for parameter estimation, significantly improving the efficiency of model calibration in engineering and scientific applications by enabling rapid identification of near-optimal parameter sets; and (2) the deep learning model effectively learns the underlying nonlinear mappings between inputs and outputs. During training, the mean squared error (MSE) loss exhibits a steady decline, with minor fluctuations in the early stages, ultimately converging to a stable value. The predicted parameter combinations show strong agreement with the reference numerical model outputs, yielding correlation coefficients exceeding 0.95.

Nitrogen-Doped tannin carbon dots anchored NiCo-LDH composites for high-performance asymmetric supercapacitors - Shirui Wang; Jianping Deng; Menghan Li; Jiande Lin; Lu Luo; Zhanhui Yuan; Wenxue Zhang; Cheng He; Guanben Du; Weigang Zhao (Chemical Engineering Journal, 2025)

A new Eötvös correction algorithm for marine shipborne gravity survey with irregular nonlinear track - Shi Liu; Lin Wu; Menghan Xi; Guocheng Mao; Lifeng Bao; Yong Wang (Acta Geophysica, 2025)

Human settlement and destructive activities disrupt the positive contribution of dust to plant biomass growth over the past 2000 years - Lin Chen; Youliang Huang; Menghan Qiu; Zhilun Li; Rui Yang; Mengjing Li; Huiling Sun; Lixiong Xiang; Shanjia Zhang; Xiaozhong Huang; Aifeng Zhou (Global and Planetary Change, 2025)

Pesticide avermectin B1a exerts cytotoxicity by blocking the interaction between mini-chromosome maintenance 6 protein (MCM6) and chromatin licensing and DNA replication factor 1 (CDT1) - Hao Yin; Yaoyao Zheng; Menghan Chen; Ming Ding; Lin Zhang; Roujia Wang; Chunyu Wang; Jing Jia; Xiaoqian Liu (Environmental Pollution, 2025)

Longitudinal plasma magnesium status during pregnancy and the risk of gestational diabetes mellitus: a prospective cohort study - Xiyu Cao; Meng Wu; Guofu Zhang; Lixia Lin; Menghan Tu; Daxiang Xiao; Chunrong Zhong; Huaqi Zhang; Siyu Yang; Jin Liu; Xu Zhang; Xi Chen; et al. (Environmental Science and Pollution Research, 2023)

Human Methylmercury Exposure and Potential Impacts in Central Tibet: Food and Traditional Tibetan Medicine - Menghan Cheng; Maodian Liu; Dou Li; Qing Luo; Zhihao Zhang; Liuliang Yuan; Chenghao Yu; Han Xie; Huiming Lin; Qianru Zhang; De Ji; Xuejun Wang (Bulletin of Environmental Contamination and Toxicology, 2021)